Strength, microstructure and nanomechanical properties of recycled aggregate concrete containing waste glass powder and steel slag powder - Zhan, Pei-min; Zhang, Xiao-xiang; He, Zhi-hai; Shi, Jin-yan; Gencel, Osman; Hai Yen, Nguyen Thi; Wang, Guo-cai (Journal of cleaner production, 2022)
The reuse of construction and demolition wastes for producing recycled aggregate concrete (RAC) is an effective way to improve building materials sustainability and reduce the environment burden. In this study, the synergistic effect of steel slag powder (SSP) and waste glass powder (GP) on the compressive strength, microstructure and nanoscale characteristics of RAC are investigated. The results indicate that SSP and GP have a significant synergistic effect in improving the performance of RACs. RAC with 10% GP and 20% SSP has the highest compressive strength, and its 28-day and 120-day compressive strengths have increased by 28.3% and 22.8% respectively relative to plain concrete. Meanwhile, the RAC with SSP and GP has a lower porosity and a high-volume fraction of high-density C–S–H, which are beneficial to improving the internal microstructure of the RAC. In addition, the incorporation of SSP and GP not only improves the microstructure of the matrix, but also reduces the width of the interface transition zone (ITZ) between the recycled aggregate and the new matrix. When 10% GP and 20% SSP are incorporated, the width of the new ITZ of RAC is reduced by 36.36%, and the average elastic modulus is increased by 64.6% compared to plain concrete. This research not only improves the performance of RAC, but also provides an effective way for the comprehensive utilization of the multiple solid wastes in concrete material. [Display omitted]